2011
DOI: 10.1111/j.1574-695x.2011.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Vγ4+T cells regulate host immune response to West Nile virus infection

Abstract: Vγ4+ cells, a subpopulation of peripheral γδ T cells, are involved in West Nile virus (WNV) pathogenesis, but the underlying mechanism is unclear. In this study, we found that WNV-infected Vγ4+ cell-depleted mice had lower viremia and a reduced inflammatory response in the brain. Vγ4+ cells produced interleukin (IL)-17 during WNV infection, but blocking IL-17 signaling did not affect host susceptibility to WNV encephalitis. We also noted that there was an enhanced magnitude of protective splenic Vγ1+ cell expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…However, no difference in the WNV burden was observed between anti-IL-17A antibody-treated and control mice (88). In contrast, our results clearly demonstrate that Il17a Ϫ/Ϫ mice are more susceptible to WNV infection.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, no difference in the WNV burden was observed between anti-IL-17A antibody-treated and control mice (88). In contrast, our results clearly demonstrate that Il17a Ϫ/Ϫ mice are more susceptible to WNV infection.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that mice treated with anti-IL-17A antibody show an approximately 20% reduced survival rate compared to the control mice after a lethal WNV challenge (88). However, no difference in the WNV burden was observed between anti-IL-17A antibody-treated and control mice (88).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although some host immune pathways have been implicated in the recognition of CHIKV and subsequent induction of protective and pathogenic responses (59,62,67,69,82,(92)(93)(94), the precise mediators and mechanisms of CHIKV pathogenesis are still relatively poorly understood. Given the prevalence of ␥␦ T cells in the skin, the primary site of CHIKV infection, and evidence that this T cell subset plays a role in the pathogenesis of other arboviruses (95)(96)(97)(98), we tested whether ␥␦ T cells played any role in the pathogenesis of CHIKV-induced disease. These studies demonstrated that CHIKV infection leads to significant increases in the prevalence of ␥␦ T cells in both the foot and draining popliteal lymph node and that the absence of these cells leads to enhanced clinical signs of disease as well as CHIKV-induced histopathologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytokine production, ␥␦ T cells have been described as a bridge between the innate and acquired immune responses by providing for the early and rapid movement and functions of key effector cells, such as neutrophils, macrophages, and NK cells, to the site of infection (74-76, 106, 107) and then downregulating the immune response after the danger has passed, to minimize potential immune-mediated injury (31,72,73,96,97). Monocytes have been shown to play a pathogenic role during CHIKV infection (66), and therefore the finding that monocyte numbers were increased in the foot/ankle of ␥␦ T Ϫ/Ϫ mice suggests that ␥␦ T cells may limit monocytic influx at day 5 and thereby decreasing the damage these cells cause within muscle tissue of the foot (Fig.…”
Section: Discussionmentioning
confidence: 99%